THE SITUATION OF THE TEACHING OF HOLISTIC AND COMPLEMENTARY PRACTICES IN UNDERGRADUATE COURSES IN NURSING, PHYSIOTHERAPY AND MEDICINE - Léia Fortes Salles; Rafael Fernandes Bel Homo; Maria Júlia Paes da Silva (Universidade Federal do Paraná, 2014)
This study aimed to analyze the situation of the teaching of Integrative and Complementary Practices in faculties of Nursing, Medicine and Physiotherapy in Brazil. The sample was constituted of public faculties and the data search occurred on the websites of the institutions investigated, between May 2012 and March 2013. Of the 209 public higher education institutions, only 43 (32.3%) offered courses related to this topic. Among these three courses, the schools of Nursing offer the most courses, followed by Medicine and Physiotherapy; 26.4%, 17.5% and 14.6%, respectively. The mean course load is 46 hours, and the majority are offered as options, with a large proportion of health professionals not studying these knowledges. The teaching institutions, which train professionals for the job market and for the Unified Health System, need to review the curriculum frameworks.